Microbiome and oral squamous cell carcinoma: a possible interplay on iron metabolism and its impact on tumor microenvironment - Arthur, Rodrigo Alex; Bezerra, Rafael dos Santos; Bianchi Ximenez, Joao Paulo; Merlin, Bruna Lais; Morraye, Raphael de Andrade; Neto, Joao Valentini; Nasser Fava, Natalia Melo; Alves Figueiredo, David Livingstone; Oliveira de Biagi Jr, Carlos Alberto; Montibeller, Maria Jara [UNESP]; Guimaraes, Jhefferson Barbosa; Alves, Ellen Gomes; et al. (Springer, 2021)
There is increasing evidence showing positive association between changes in oral microbiome and the occurrence of oral squamous cell carcinoma (OSCC). Alcohol- and nicotine-related products can induce microbial changes but are still unknown if these changes are related to cancerous lesion sites. In an attempt to understand how these changes can influence the OSCC development and maintenance, the aim of this study was to investigate the oral microbiome linked with OSCC as well as to identify functional signatures and associate them with healthy or precancerous and cancerous sites. Our group used data of oral microbiomes available in public repositories. The analysis included data of oral microbiomes from electronic cigarette users, alcohol consumers, and precancerous and OSCC samples. An R-based pipeline was used for taxonomic and functional prediction analysis. The Streptococcus spp. genus was the main class identified in the healthy group. Haemophilus spp. predominated in precancerous lesions. OSCC samples revealed a higher relative abundance compared with the other groups, represented by an increased proportion of Fusobacterium spp., Prevotella spp., Haemophilus spp., and Campylobacter spp. Venn diagram analysis showed 52 genera exclusive of OSCC samples. Both precancerous and OSCC samples seemed to present a specific associated functional pattern. They were menaquinone-dependent protoporphyrinogen oxidase pattern enhanced in the former and both 3 ',5 '-cyclic-nucleotide phosphodiesterase (purine metabolism) and iron(III) transport system ATP-binding protein enhanced in the latter. We conclude that although precancerous and OSCC samples present some differences on microbial profile, both microbiomes act as iron chelators-like potentially contributing to tumor growth.
Keywords: Microbiome; Oral squamous cell carcinoma; Alcohol; Cigarette; Functional pathways prediction; Iron(III) transport system